2013
DOI: 10.1136/tobaccocontrol-2012-050672
|View full text |Cite
|
Sign up to set email alerts
|

The carbon footprint of behavioural support services for smoking cessation

Abstract: All smoking cessation services had low emissions compared to the health gains produced. Text message support had the lowest emissions of the services evaluated. Smoking cessation services have small carbon footprints and were cost-effective after accounting for the societal costs of greenhouse gas emissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…Beyond the direct carbon footprint associated with each behavior, research has also documented the carbon footprint of interventions, such as behavioral support for smoking cessation modes of delivery. The respective carbon footprint of text messages, telephone, group and individual counselling were 0.8, 0.9, 16.1, and 16.4 tonnes of CO2 equivalent for 1000 smokers, respectively [146]. This study showed that all modes of delivery are not equal in terms of environmental impact.…”
Section: Amplification Role Of Health Behaviorsmentioning
confidence: 72%
“…Beyond the direct carbon footprint associated with each behavior, research has also documented the carbon footprint of interventions, such as behavioral support for smoking cessation modes of delivery. The respective carbon footprint of text messages, telephone, group and individual counselling were 0.8, 0.9, 16.1, and 16.4 tonnes of CO2 equivalent for 1000 smokers, respectively [146]. This study showed that all modes of delivery are not equal in terms of environmental impact.…”
Section: Amplification Role Of Health Behaviorsmentioning
confidence: 72%
“…Sixteen articles were excluded because they had no primary study, contained no CF calculation, or had no VC topic. Finally, 16 studies were included in the systematic review [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The search update includes 144 titles and abstracts.…”
Section: Resultsmentioning
confidence: 99%
“…Verificou-se o predomínio nos estudos dos últimos cinco anos da abordagem individual ao tabagismo (35,51% dos artigos) com intervenções breves, aplicação de entrevista motivacional, utilização da estratégia dos 5A's e Terapia cognitivo-comportamental (TCC) com apoio de equi-pe multiprofissional durante consulta de saúde. Destaca-se a realização de espirometria para controle de emissão de carbono visando à sensibilização do paciente com relação à sua função respiratória [16][17][18][19] .…”
Section: Base De Dadosunclassified
“…A espirometria, exame através do qual se pode estimar a emissão de carbono pelo paciente tabagista, é também apoio extra para a cessação tabágica 17 . CO-oximetria mostrou-se de baixo custo, não invasiva e rápida permitindo abordar os fumantes na APS diante de sua eficácia já atestada como auxiliar no reforço de atividades de cessação do tabagismo,promovendo redução do hábito com maior custo-efetividade naqueles que utilizam estratégias de apoio como mensagens de texto e aconselhamento individual ou em grupo, além de surtir efeitos em intervenção motivacional entre fumantes em condições reais de prática clínica 8,[17][18][19] .…”
Section: Categorizaçãounclassified